Cover Picture: Magnetic Dextran Nanoparticles That Bear Hydrophilic Porphyrin Derivatives: Bimodal Agents for Potential Application in Photodynamic Therapy (ChemPlusChem 9/2015). Issue 9 (September 2015) - Mbakidi, Jean‐Pierre; Brégier, Frédérique; Ouk, Tan‐Sothea; Granet, Robert; Alves, Sandra; Rivière, Eric; Chevreux, Sylviane; Lemercier, Gilles; Sol, Vincent
<x xml:space="preserve">Abstract</x> The cover picture shows the magnetic and optical properties of iron oxide, dextran‐based superparamagnetic nanoparticles bearing hydrophilic porphyrin derivatives, which are new bimodal contrast agents in magnetic resonance imaging and photosensitizers in photodynamic therapy. The therapeutic potential of these nanoparticles was evaluated in vitro against the HaCaT cell line. More details can be found in the Full Paper by Vincent Sol et al. on page 1416 in Issue 9, 2015. (DOI: 10.1002/cctc.201500087).